Strategi Pelayanan Sekretariat Dewan Perwakilan Rakyat Daerah di Kabupaten Bintan - Anggraini, Riang; Subiyakto, Rudi; Ilmiah Rivai, Nur (Universitas Serang Raya, 2024)
DPRD as part of regional government administration has an important task in increasing efficiency, productivity and accountability in government administration. Quality services from the Bintan Regency DPRD Council Secretariat are very important to ensure effective and efficient DPRD performance. This research aims to determine the service strategy carried out by the secretariat of the Bintan Regency DPRD council. This research uses a qualitative descriptive research method. Primary and secondary data are data sources in research. Research results (1) The implementation of organizational strategy can be seen from the preparation of Standard Operating Procedures (SOP) which provide clear guidance for DPRD members in carrying out their duties. (2) the program strategy is implemented through the implementation of an information management system, provision of better information services, as well as training and guidance for DPRD members. (3) human resources (HR) support strategies are carried out with selective recruitment, continuous training, and development of skills and competencies. (4) institutional strategies are implemented through providing logistical and administrative support, preparing activity agendas, routine coordination mechanisms, and appointing inter-departmental coordinators. In conclusion, the implementation of these strategies has improved the quality of DPRD council secretariat services to members of the Bintan Regency DPRD